2022
DOI: 10.1186/s12864-022-08418-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of linkage disequilibrium patterns between structural variants and single nucleotide polymorphisms in three commercial chicken populations

Abstract: Background Structural variants (SV) are causative for some prominent phenotypic traits of livestock as different comb types in chickens or color patterns in pigs. Their effects on production traits are also increasingly studied. Nevertheless, accurately calling SV remains challenging. It is therefore of interest, whether close-by single nucleotide polymorphisms (SNPs) are in strong linkage disequilibrium (LD) with SVs and can serve as markers. Literature comes to different conclusions on whethe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…Considering the constraints of SNP arrays and the reduction of DNA sequencing costs, NGS-based WGS approach is now the most popular tool to infer the evolutionary history of chicken genomes, to assess the genetic diversity and population genetic structure at regional, continental, and global scales, to identify the genetic controls of specific traits of interest, and to screen for the signatures of selection for productive traits and environmental adaptation [Rubin et al, 2010;Mugal et al, 2013;Wang MS et al, 2015, 2016a, 2016bGuo X, , 2022Guo Y et al, , 2021Zhang et al, 2016Zhang et al, , 2022Li D et al, , 2019Boschiero et al, 2018;Derks et al, 2018;Lawal et al, 2018Lawal et al, , 2020Sohrabi et al, 2018;Almeida et al, 2019;Talebi et al, 2020;Tiley et al, 2020;Wang Q et al, 2020;Gheyas et al, 2021Gheyas et al, , 2022Li YD et al, 2021;Mariadassou et al, 2021;Rostamzadeh Mahdabi et al, 2021;Tan et al, 2021;Yang Z et al, 2021;Asadollahpour Nanaei et al, 2022;Chen X et al, 2022;Gao et al, 2022;Geibel et al, 2022;Li Y et al, 2022;Sun et al, 2022;Wang S et al, 2022;Xu et al, 2022;Yuan J et al, 2022;Zeng et al, 2022].…”
Section: Wgs-based Population Genome Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the constraints of SNP arrays and the reduction of DNA sequencing costs, NGS-based WGS approach is now the most popular tool to infer the evolutionary history of chicken genomes, to assess the genetic diversity and population genetic structure at regional, continental, and global scales, to identify the genetic controls of specific traits of interest, and to screen for the signatures of selection for productive traits and environmental adaptation [Rubin et al, 2010;Mugal et al, 2013;Wang MS et al, 2015, 2016a, 2016bGuo X, , 2022Guo Y et al, , 2021Zhang et al, 2016Zhang et al, , 2022Li D et al, , 2019Boschiero et al, 2018;Derks et al, 2018;Lawal et al, 2018Lawal et al, , 2020Sohrabi et al, 2018;Almeida et al, 2019;Talebi et al, 2020;Tiley et al, 2020;Wang Q et al, 2020;Gheyas et al, 2021Gheyas et al, , 2022Li YD et al, 2021;Mariadassou et al, 2021;Rostamzadeh Mahdabi et al, 2021;Tan et al, 2021;Yang Z et al, 2021;Asadollahpour Nanaei et al, 2022;Chen X et al, 2022;Gao et al, 2022;Geibel et al, 2022;Li Y et al, 2022;Sun et al, 2022;Wang S et al, 2022;Xu et al, 2022;Yuan J et al, 2022;Zeng et al, 2022].…”
Section: Wgs-based Population Genome Analysesmentioning
confidence: 99%
“…These two analyses clearly demonstrated the power of the WGS data in CNV identification and functional annotation. Last but not least, the possibility of identifying SVs, though challenging for calling accuracy, was demonstrated from the NGS-WGS of commercial chicken genomes, among which deletions were believed to be more accurately detected compared with duplications, inversions, and translocation breakpoints [Geibel et al, 2022].…”
Section: Wgs-based Population Genome Analysesmentioning
confidence: 99%
“…It is worth noting the unique pedigree structure in the data set (127 trios) provided an independent measure of quality evaluation (i.e. Mendelian errors), but also the sequencing was done at relatively high depth (mean sequencing depth = 26X), compared to other studies that investigated SVs in livestock species [33][34][35][36]. Detection of SVs can bene t from high coverage sequencing data in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al (2021) found that, in humans, about half of their structural variants were in what they term strong to moderate (r 2 > 0.5) linkage disequilibrium with at least one surrounding variant. In the chicken, Geibel et al (2022) found that deletions were well tagged by single nucleotide variants, with linkage disequilibrium comparable to the values between pairs of single nucleotide variants, but that other structural variants types (duplications, inversions, and translocations) were poorly tagged. In this case, however, the structural variants were called with short read sequencing and relatively low coverage, that likely has low accuracy for duplications, inversions and translocations.…”
Section: Inclusion Of Undetected Genetic Variationmentioning
confidence: 96%
“…Part of the problem is that structural variants tend to occur in repetitive regions of the genome that are hard to sequence and genotype, and part that structural variants can the genotyping of neighbouring variants, by changing flaking sequence, order of the genetic map, causing null alleles or artificial heterozygotes by duplication and so on. Thus, the low linkage disequilibrium around many structural variants may be partially due to biology and partially due to technical difficulties (Geibel et al, 2022;Yan et al, 2021).…”
Section: Inclusion Of Undetected Genetic Variationmentioning
confidence: 99%